Sustainable tourism practices adopted by the hotel sector in Zimbabwe. Hotel managers perceptions - Muchingami, Abraham; Basera, Vitalis; Mashoko, Dennis; Bhasopo, Trinity (Goodwood Publishing, 2025)
Purpose: This study investigated hotel managers perceptions of sustainability practices adopted in the hotel sector in Zimbabwe, focusing on hotels in Mutare. The issue of sustainable business practices is driving modern-day business operations, and hotels are leading the adoption of sustainable tourism practices. Managers perceive the adoption of sustainable tourism practices in varied or indifferent manners. This study focused on identifying the extent to which hotels in Zimbabwe have adopted sustainable practices, the impacts of adopting these practices, the challenges hotels face when adopting these practices, and the strategies hotels implement when adopting these practices. Research Methodology: A qualitative research design was used to understand hotel managers’ perceptions regarding the adoption of sustainable tourism practices, with interviews being used to collect data. The study’s population comprised managerial employees and supervisors of selected hotels in Mutare, Zimbabwe. Results: The findings revealed that the implementation of sustainable practices has a positive impact on hotel operations in terms of reduced consumption of water and energy, waste reduction, promotion of the local economy, and empowerment of societies. Conclusion: Hotels in Mutare perceive sustainability as highly beneficial, not only for cost savings and environmental protection but also for competitive advantages. Training, guest involvement, and certification emerged as essential strategies, whereas resistance, high costs, and lack of knowledge were noted as barriers. Limitations: The study used only hotel managers in Mutare to represent all hotel managers in Zimbabwe, and it was purely qualitative. Contributions: The study concluded that waste management undertakings, such as recycling, re-use, or sale of processed or unprocessed waste substances, can also contribute towards efficiency.